1984
DOI: 10.3928/0191-3913-19840101-04
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Anomalies Associated With the Fetal Alcohol Syndrome

Abstract: Anterior segment anomalies were noted in eight children diagnosed as having the fetal alcohol syndrome. Peters' and Axenfeld's anomalies were among the specific defects noted. Four children have maintained clear corneal grafts. A teratogenic action of alcohol during a critical period of development of anterior chamber structures is suggested as an etiologic factor. It is proposed that the varied types and severity of abnormalities noted might result from differences in blood alcohol levels, timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Finally, the mean follow-up per patient was shorter in all of these studies than our series. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23][24][25][26]28 The visual outcomes were poor for the majority of the eyes in our series for a variety of reasons. First, many of these eyes had preexisting ocular abnormalities apart from the characteristic structural defects of Peters anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mean follow-up per patient was shorter in all of these studies than our series. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23][24][25][26]28 The visual outcomes were poor for the majority of the eyes in our series for a variety of reasons. First, many of these eyes had preexisting ocular abnormalities apart from the characteristic structural defects of Peters anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…When the opacity obstructs the passage of light through the pupil, penetrating keratoplasty may be indicated. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Postoperative optical correction and occlusion therapy are necessary to prevent abnormal visual experience and deprivation amblyopia.…”
mentioning
confidence: 99%
“…Our results are consistent with clinical case reports of poor visual acuity in children with FAS. [3][4][5][6][7] We examined whether lower TAC scores among alcohol-exposed infants might be due to a developmental delay that affects the infant's ability to attend appropriately to the visual acuity cards. But the effect of prenatal alcohol exposure on acuity was independent of the infant's performance on the FTII, a valid measure of infant visual information processing that also depends on the infant's ability to attend to visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of the eye were noted in the earliest reports of FAS, and case studies have documented numerous ophthalmologic abnormalities. [2][3][4][5][6][7] In a case study of 30 children with FAS referred for ophthalmologic evaluation, 90% had some ophthalmologic abnormality, and more than half of those affected had impaired visual acuity. 5,6 Another study found poorer acuity in 9 of 10 children with FAS.…”
mentioning
confidence: 99%
“…If the teratogenic effect of alcohol occurs before the initial mesenchyme migration to form the corneal endothelium, keratocytes and iris stromal cells (about six weeks gestation), the endothelium, and Descemet's membrane might reach only the peripheral cornea. 5 Stromland' in a review of ocular abnomalies in 30 cases reported that 48% of the eyes showed hypoplasia of the optic nerve head and 49% had abnormal tortuosity of the retinal arteries. However, only 10% had anterior segment and media abnormalities (microcornea, cataract, iris defects, and persistent hyaloid artery), and none of them had either Peters' or Axenfeld's anomaly.…”
Section: Discussionmentioning
confidence: 99%